2021
DOI: 10.1021/acsabm.0c01630
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Gelatin Hydrogels in Nanomedicine Applications

Abstract: Gelatin based hydrogels are often incorporated with supporting materials such as chitosan, poly­(vinyl alcohol), alginate, carbon nanotubes, and hyaluronic acid. These hybrid materials are specifically of interest in diversified nanomedicine fields as they exhibit unique physicochemical properties, antimicrobial activity, biodegradability, and biocompatibility. The applications include drug delivery, wound healing, cell culture, and tissue engineering. This paper reviews the various up-to-date methods to fabri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 172 publications
0
47
0
Order By: Relevance
“…Obtaining GEL from COL requires breaking the bonds that stabilize the structure from a pre-treatment by means of acids, bases or enzymes. In this sense, type A GEL (isoelectric point 8–9) is obtained after an acid treatment of COL, and type B GEL (isoelectric point 4–5) is obtained with an alkaline treatment [ 74 , 152 ]. The amines present in the lysine side chains help the GEL to adhere to the carboxyl groups of the tissue surface molecules [ 75 ].…”
Section: Methodsmentioning
confidence: 99%
“…Obtaining GEL from COL requires breaking the bonds that stabilize the structure from a pre-treatment by means of acids, bases or enzymes. In this sense, type A GEL (isoelectric point 8–9) is obtained after an acid treatment of COL, and type B GEL (isoelectric point 4–5) is obtained with an alkaline treatment [ 74 , 152 ]. The amines present in the lysine side chains help the GEL to adhere to the carboxyl groups of the tissue surface molecules [ 75 ].…”
Section: Methodsmentioning
confidence: 99%
“…Salahuddin et al prepared a light-controlled hydrogel. When exposed to light, the mesh of the hydrogel changes, altering the diffusion rate of the molecules being convenient for the controlled release of the drug [134]. Yang et al prepared an antiopal microsphere and used its nanoporous structure to load drugs injected into the joint cavity.…”
Section: Drug Delivery and Tissue Engineeringmentioning
confidence: 99%
“…The key to DNA biosensors is the fusion of materials with specific probe DNA or single-stranded DNA (ssDNA) [ 103 ]. Gelatin can be a promising material for DNA biosensors due to its good biocompatibility, biodegradability, biological activity, exceptional cell/tissue attraction, and extraordinary physiochemical characteristics [ 104 ]. It has been reported that GelMA and DNA can be used as a biosensor for DNA hybridization [ 105 ].…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%